Acetylation phenotype variation in patients with allergic contact dermatitis - Rafi Abdul Majeed Al-Razzuqi; Abdul-Kareem Naji Al-Kufi; Khansa' Abdul Ameer Al-Yaser; Yassin Farhan Al-Rekabi (Indian Journal of Dermatology, 2019)
Background: Studies have been done on acetylation phenotype in different diseases but not with allergic contact dermatitis (ACD). Patients and Methods: Thirty-five ACD patients and 67 healthy volunteers were enrolled in the study. After an overnight fast, each participant received a single oral dose of 100 mg of dapsone. Three hours later, a blood sample was taken from each participant and plasma was separated to determine dapsone and its metabolite (monoacetyldapsone) using high-performance liquid chromatography. Results: Nearly 60% of the patients (21 out of 35 ACD patients) were slow acetylators compared with 72% (48 out of 67 controls), and a statistically significant difference was found. No association between the acetylator status and personal/family history of allergy, patch test positivity, and even the sites of ACD was detected. In the ACD patients with slow acetylators, the lesions of dermatitis presented mainly on the face, neck, and upper limbs, while those with rapid acetylator have predominant lesions in the chest, oral region, and axillae. Conclusion: A rapid acetylator status might predispose to ACD without influencing other features of this disease.